Pengelolaan Keuangan Wisata Religi Tebuireng Dalam Pemberdayaan Ekonomi Masyarakat - Khafifi, Imam Khakam; Askafi, Eka; Arisyahidin, Arisyahidin (Otonomi, 2024)
Micro, small and medium enterprises or what are usually called UMKM are one of the important aspects in advancing a country's economy. In fact, developed countries such as America and China are able to become developed countries because their economic sectors are supported by UMKM. Indonesia is currently in a phase of economic development to move from developing countries to developed countries. In 2022, the Indonesian economy can be said to increase by 5.31 percent compared to 2021, which reached 3.70 percent. This religious tourism has caused significant changes in the economic sector of the community in Tebuireng, Jombang. Before this tourism, the Tebuireng area was an ordinary Islamic boarding school area. After the death of KH. Abdurahman Wahid (Gus Dur) people started arriving to go on a pilgrimage to Gus Dur's grave. Gus Dur's family thought that this phenomenon would only last for a short time, but unexpectedly people continued to come to Gus Dur's grave. This resulted in very high economic progress. Traders continue to appear, there are public toilet facilities, prayer rooms and accommodation which can boost the income of the Tebuireng community. Of course, this is a breath of fresh air for the Jombang district government because it will increase the per capita income of the Jombang region